Geographic approximation to the feminicides in the Boyacá department in Colombia between 2017 and 2021. A review of the Nobsa case - Alvarez Moreno, Blanca Yanneth (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper aims to make a geographic approximation to the understanding ofthe feminicide phenomenon in Boyacá, Colombia, based on the events that took place in this department between 2017 and 2021. Therefore, a documentary review was made to know the context of feminicides in Colombia, especially in the Boyacá department. Moreover, anin-depth interview was conducted to collect the life story of a woman inhabitant of the region who is a mother head of household and suffered the feminicide of her underage daughter in2017. Subsequently, the secondary information was triangulated with the testimony of the interviewee to identify patterns in this conduct. The results suggest that, even though thefeminicide rates in the department are low in comparison to other departments, it is necessary to attend to and prevent other types of violence urgently, such as physical or sexual, since they can trigger this type of murders and have been increasing in the region during the last years.